2013
DOI: 10.2503/jjshs1.82.203
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Sterile Anthers and Inheritance of Cytoplasmic-genetic Male Sterility in Zygotic Seedlings of Polyembryonic Acid Citrus

Abstract: In acid citrus, genetic control of male sterility, an important characteristic for breeding seedless fruit cultivars, is not precisely known because of the presence of barriers such as polyembryony and a long juvenile phase. In this study, 22 crosses with 16 male-fertile acid citrus cultivars were carried out and the zygotic seedlings were grafted onto adult satsuma mandarin trees to enhance flowering. Four crosses with two monoembryonic and male-sterile citrus plants (HY16 and 'Kiyomi') were also carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Male sterility and fertility segregate in the F 1 populations of a cross between different varieties and selected strains harboring the Kishu-cytoplasm ( Yamamoto et al., 1992 ; Yamamoto et al., 1997 ; Nakano et al., 2001 ; Dewi et al., 2013 ; Goto et al., 2016 ). Specifically, the genomes in Japanese varieties and selected strains were constituted by genomic fragments (i.e., haplotype blocks) that are derived from limited founders ( Imai et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Male sterility and fertility segregate in the F 1 populations of a cross between different varieties and selected strains harboring the Kishu-cytoplasm ( Yamamoto et al., 1992 ; Yamamoto et al., 1997 ; Nakano et al., 2001 ; Dewi et al., 2013 ; Goto et al., 2016 ). Specifically, the genomes in Japanese varieties and selected strains were constituted by genomic fragments (i.e., haplotype blocks) that are derived from limited founders ( Imai et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports suggested the involvement of nuclear genes in male sterility [ 5 , 35 – 38 ]. Guo et al [ 7 , 8 ] and Zheng et al [ 11 ] have tried to induce male sterility by replacing the cytoplasm by that of Satsuma type with cell fusion in Hirado buntan and Zheng et al observed aborted pollen grains in the regenerated plants [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two factors may contribute to the high level of heterozygosity of the yuzu genome. First, yuzu is predominantly reproduced through asexual nucellar embryony, a sporophytic apomixis (Dewi et al, 2013). Nucellar embryony is widespread among most commercial cultivars of sweet orange, mandarin, grapefruit, and lemon (Xu et al, 2021).…”
Section: Identification Of Putative Parental Species Of Yuzu By Seque...mentioning
confidence: 99%